LEGALITAS ABORSI YANG DILAKUKAN OLEH ANAK KORBAN PEMERKOSAAN DI INDONESIA - Nafaya Ramadhani Bidari, (2021)
This study aims to find out how the legal protection for child victims of rape who have an abortion in the Indonesian legal system. The problem of abortion itself often occurs in Indonesia where abortion is prohibited and can lead to criminal acts for those who commit it. Abortion is an act of killing the fetus. In Indonesia, there are not a few children who are involved in abortion cases, with the background that the child has been abused. In this study, the position of abortion against a child requires him to perform this action to prioritize life safety, and the basis for the abortion. Abortion can be performed for certain reasons stipulated in Law Number 36 of 2009 concerning health. This study uses a normative judicial method which uses literature and legislation to examine this research, this study aims to determine the rights of minors and their protection Key words: Child, Abortion, Rape.